Effect of cultivation system on the methane emission from rice soil - Fazli, Pardis; Che Man, Hasfalina; Mohamed Zawawi, Mohamed Azwan; Idris, Azni; Md. Shah, Umi Kalsom; Wayayok, Aimrun (2012)
Methane (CH4) is a potent green house gas and second in importance after carbon dioxide (CO2) with a global warming potential of 25 times more than CO2. Paddy fields are important sources of methane and contribute in approximately 15–20% of the annual global methane efflux. Cultivation systems can affect the methane emission by their different water management and practices. One of the cultivation methods is the system of rice intensification (SRI). Considering the water management system and the plant density, in this method less methane is expected compared to conventional cultivation method. Consequently, current study has been done to evaluate the influence of two SRI methods on methane emission. For this purpose, closed chamber applied to measure methane emission. As a result, conventional method showed the highest total methane flux with emitting of 26.4 g CH4 m-2 compared to original SRI treatments and triangular pattern (7.7 g CH4 m-2 and 8.9 g CH4 m-2). The pattern of water management was the most influencing factor lead to lower methane emission in SRI treatments. In addition, SRI treatments produced higher yield than the conventional method. This could be a promising result toward a sustainable rice production.